Latvia Diagnostic Review of Consumer Protection and Financial Capability : Volume 1. Key Findings and Recommendations - World Bank (World Bank, Washington, DC, 2017)
The Diagnostic Review of Consumer Protection and Financial Capability in Latvia is the ninth report in a World Bank-sponsored pilot program to assess consumer protection in financial services in developing and middle-income countries. The publication of the Diagnostic Review for Latvia aims to enhance development of financial consumer protection both in Latvia and worldwide. The Review is presented in two volumes. Volume I notes the importance of consumer protection in financial services, describes the Government's policy strategy for financial consumer protection, provides statistics on the size and growth of the retail financial sector in Latvia, and sets out the key findings and recommendations of the Review. Volume II provides an assessment of the Latvian consumer protection institutional and legal framework and practices against the benchmark of Good Practices for six segments of the financial sector—banking, nonbanking credit institutions, securities, insurance, private pensions and credit reporting systems.